O cultivo agroecológico de Manihot Esculenta Crantz: um estudo de caso em uma unidade de produção familiar - SACRAMENTO, Arinéia Ferreira (2024)
This work had as objective to accomplish a case study in a family production unit, referring to the agroecological cultivation of cassava (Manihot esculenta Crantz). The research was done in the rural community Ramal do Maúba in the Municipality of Abaetetuba, Pará. The Participatory Rural Diagnosis was used as research methodology, consisting of analyzes such as: participant observation, semi-structured interview, production flowchart and transversal walk. It was verified the importance of the cassava culture for the family production, in the productive unit studied, as well as the need of organizational strategies, aiming at the strengthening of the productive activity of the cassava culture, such as: the effectiveness of the public policies focused on basic production and the creation of an association in the community that would contribute to the processing, marketing and processing of cassava products.